Effectiveness of Applying Emotional Regulation Technologies in Various Sports (Zien Journal of Social Sciences and Humanities, 2025)
The article discusses the effectiveness of using emotional management technologies in sports. The content of the analysis is also described, such as the effectiveness of using emotional management technologies in various sports, their dependence on the characteristics and requirements of sports, a clear understanding of the psychological needs of athletes and the use of techniques adapted to them, helping to improve their performance during competitions, and the important role of emotional management technologies in increasing the mental endurance of athletes.